1995
DOI: 10.3758/bf03197229
|View full text |Cite
|
Sign up to set email alerts
|

Visual distinctivenesscan enhance recency effects

Abstract: Experimental efforts to meliorate the modality effect have included attempts to make the visual stimulus more distinctive. McDowdand Madigan (1991) failed to find an enhanced recency effect in serial recall when the last item was made more distinct in terms of its color. In an attempt to extend this finding, three experiments were conducted in which visual distinctiveness was manipulated in a different manner, by combining the dimensions of physical size and coloration (i.e., whether the stimuli were solid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, there is a danger of circularity in this argument unless we can produce an a priori definition of distinctiveness, and attempts to generalise this concept have met with little success. For example, it has not been possible to create strong recency effects for visually presented lists by adding distinctive visual features to terminal list items (LeCompte, 1992;McDowd & Madigan, 1991) although weak effects have been reported by Bornstein, Neely, and LeCompte (1995). Within the auditory domain, the temporal distinctiveness hypothesis cannot explain the lack of strong recency effects for highly discriminable nonspeech auditory stimuli (Frankish, 1996;Surprenant et al, 1993).…”
Section: Criticisms Of the Pas Account Of Auditory Recencymentioning
confidence: 92%
“…However, there is a danger of circularity in this argument unless we can produce an a priori definition of distinctiveness, and attempts to generalise this concept have met with little success. For example, it has not been possible to create strong recency effects for visually presented lists by adding distinctive visual features to terminal list items (LeCompte, 1992;McDowd & Madigan, 1991) although weak effects have been reported by Bornstein, Neely, and LeCompte (1995). Within the auditory domain, the temporal distinctiveness hypothesis cannot explain the lack of strong recency effects for highly discriminable nonspeech auditory stimuli (Frankish, 1996;Surprenant et al, 1993).…”
Section: Criticisms Of the Pas Account Of Auditory Recencymentioning
confidence: 92%
“…Participants lurking on the online-news website are unlikely to feel fettered by the normative pressure from a numerical-majority group, and their cognitive process would be affected by perceptual characteristics of stimuli. Previous studies on visual attention propose that greater cognitive resource is allotted to visually distinctive stimuli than to mundane ones (e.g., salience effect, Taylor, Crocker, Fiske, Sprinzen, & Winkler, 1979; distinctiveness effect, Bornstein & Neely, 1995). Given that the minority opinion in our online-news website is more discernible than the majority opinion, participants may direct their attention to the minority one and deliberate their arguments.…”
Section: Discussionmentioning
confidence: 99%
“…Although Frankish produced the modality effect, it was somewhat diminished, possibly because of the enhanced visual recency effects that were generated by the presentation methodology. Bornstein, Neely, and LeCompte (1995) also demonstrated visual recency effects via manipulation of presentation, but they presented lists with last items that were physically different from the other list items. Frankish and Bornstein et al showed that the presentation method for stimuli can influence visual recency effects, which help determine the magnitude of the modality effect (i.e., low visual recency helps create a large modality effect).…”
Section: Influence Of Recall Procedures On the Modality Effect With Nmentioning
confidence: 99%
“…Because enumeration was a relatively novel presentation method, we evaluated recency effects by comparing recall accuracy across Positions 8 and 9 for all four conditions. This method is referred to as the kick-up method, and it examines the gain in recall for the last item relative to recall for the penultimate item (e.g., Battachi et al, 1990;Bornstein et al, 1995).…”
Section: Recency Effectsmentioning
confidence: 99%
See 1 more Smart Citation